Intermittent Contact Alternating Current Scanning Electrochemical Microscopy: A Method for Mapping Conductivities in Solid Li Ion Conducting Electrolyte Samples - Catarelli, Samantha Raisa; Lonsdale, Daniel; Cheng, Lei; Syzdek, Jaroslaw; Doeff, Marca (Frontiers in Energy Research, 2016)
Intermittent contact alternating current scanning electrochemical microscopy (ic-ac-SECM) has been used to determine the electrochemical response to an ac signal of several types of materials. A conductive gold foil and insulating Teflon sheet were first used to demonstrate that the intermittent contact function allows the topography and conductivity to be mapped simultaneously and independently in a single experiment. Then a dense pellet of an electronically insulating but Li-ion conducting garnet phase, Al-substituted Li7La3Zr2O12 (LLZO), was characterized using the same technique. The polycrystalline pellet was prepared by classical ceramic sintering techniques and was comprised of large ( 150 μm) grains. Critical information regarding the contributions of grain and grain boundary resistances to the total conductivity of the garnet phase was lacking due to ambiguities in the impedance data. In contrast, the use of the ic-ac-SECM technique allowed spatially resolved information regarding local conductivities to be measured directly. Impedance mapping of the pellet showed that the grain boundary resistance, while generally higher than that of grains, varied considerably, revealing the complex nature of the LLZO sample.